Money and costly credit - Mei Dong (Bank of Canada, 2011)
I study an economy in which money and credit coexist as means of payment and the settlement of credit requires money. The model extends recent developments in microfounded monetary theory to address the choice of payment methods and the effects of inflation. Whether a buyer uses money or credit depends on the fixed cost of credit and the inflation rate. In particular, inflation not only makes money less valuable, but also makes credit more expensive because of delayed settlement. Based on quantitative analysis, the model suggests that the relationship between inflation and credit exhibits an inverse U-shape which is broadly consistent with anecdotal evidence. Compared to an economy without credit, allowing credit as a means of payment has three implications: [1] it lowers money demand at low to moderate inflation rates; [2] it improves society's welfare when the inflation rate exceeds a specific threshold; and [3] it can raise the welfare cost of inflation for some reasonable values of the credit cost parameter.
Keywords: E41; E50; 330; Credit and credit aggregates; Inflation; costs and benefits; Geldwirtschaft; Kredit; Inflation; Zahlungsverkehr; Geldtheorie